Application of Validated High-performance Liquid Chromatography Method for Degradation Study of Saxagliptin and Metformin HCl: Application of Validated High-performance Liquid Chromatography Method for Degradation Study of Saxagliptin and Metformin HCl - Sheikh, Imran A. (International Journal of Pharmaceutical & Biological Archive, 2018)
A novel and simple reversed-phase liquid chromatographic method has been established for the determination of saxagliptin and metformin HCl Saxagliptin and metformin HCl is used to control Type 2 diabetes. The proposed work was performed on Young Lin (S.K) isocratic System UV Detector. Saxagliptin and metformin HCl is used to control Type 2 diabetes. The proposed work was performed on Young Lin (S.K) isocratic System UV Detector C18 column (150 mm Ã— 4.6 mm). A mixture of potassium phosphate, mobile phase in this method with flow rate of 0.7 mL/min (UV detection at 203 nm) and the method was validated as per the ICH guidelines. Forced degradation studies were performed by exposing the drug saxagliptin and metformin HCl to acidic, alkaline, oxidation, and thermal stress degradations. The proposed reversed-phase-high-performance liquid chromatography method was found to be robust and specific, and this method is suitable for the assay of pharmaceutical dosage forms as well as kinetic studies.